TRANSFORMASI PEMBELAJARAN SASTRA DALAM MENGEMBANGKAN KEWIRAUSAHAAN DI ERA INDUSTRI KREATIF - Suhariyanti, Suhariyanti (Universitas Dharmawangsa, 2025)
The era of the creative industry presents significant opportunities to integrate literary learning with entrepreneurship. This study explores the transformation of literary education as an effort to develop entrepreneurial potential among students. Literature, as a form of creative expression, plays a strategic role in fostering creativity, critical thinking skills, writing proficiency, and communication abilities, which are essential elements in entrepreneurship. Through an interdisciplinary approach, literary learning can be designed to involve the analysis of literary works, narrative creation, and the exploration of innovation themes relevant to the creative industry. This study also identifies project-based literary learning models that encourage students to create original works with economic potential, such as film scripts, dramas, short stories, novels, or story-based products. The findings indicate that the transformation of literary learning not only enriches aesthetic appreciation but also provides a foundation for students to utilize their creative abilities in generating business opportunities. Therefore, the integration of literature and entrepreneurship holds the potential to create a generation that is creative, innovative, and competitive in the era of the creative industry.